Intertemporal Labor Supply and Long Term Employment Contracts - Abowd, John M.; Card, David (American Economic Review, 1986)
In this paper we compare the implications of a symmetric information contracting model and a dynamic labor supply model for changes in individual earnings and hours over time. The critical distinction between these models is whether earnings represent optimal consumption or payment for current labor services. We develop a simple test between labor supply and contracting models based on the relative variability of earnings and hours with respect to changes in productivity. If earnings represent consumption then changes in productivity generate smaller changes in earnings than hours. The opposite is true in the labor supply model. We apply our test to longitudinal data on male household heads fran the Panel Study of Income Dynamics and the National Longitudinal Survey of Older Men, focusing on individuals who do not change employers during the survey period. Neither model fits the data well. In both surveys, however, the contrihition of changes in productivity to changes in earnings is greater than the contribution to changes in hours. The data are more consistent with a labor supply interpretation, although the estimated labor supply elasticities suggest that changes in hours occur at fixed wage rates.